Phenol and Flavonoid Amounts, Antioxidant and Antibacterial Potencies of Xanthoparmelia stenophylla (Ach.) Ahti&D. Hawksw. - KINALIOĞLU, Kadir; AYDIN, Sinem; İLHAN, Özge; YILMAZ, Zeynep (Afyon Kocatepe Üniversitesi, 2016)
Xanthoparmelia stenophylla is traditionally utilized for the cure of snake bites and venearal diseases like syphilis. X. stenophylla have different colouring compounds and can be used as dye sources. Different extracts obtained from X. stenophylla were tested in terms of antioxidant and antibacterial traits. Phenol and flavonoid concentrations of the extracts were also determined. Chloroform and acetone were used assolvents in the soxhlet extraction. While bacteria‐inhibiting efficacy was detected with the disc diffusion technique. The antioxidant property was determined through DPPH radical scavenging activity, reducing power and metal chelating activity. Chloroform extract was most effective against Bacillus megaterium with an inhibition zone of 25 mm. Both the acetone and chloroform extracts were not effective against Klebsiella pneumonia. The highest phenolic content was found in the chloroform extract (42.58±0.47 µg/mL) and the highest flavonoid content was obtained in the acetone extract (113.56±1.02 µg/mL).  DPPH activity of lichen extracts was between 9.33‐33.84%. The reducing activity extracts and standards were found the given order: BHT>Rutin>Chloroform extract of X. stenophylla> Acetone extract of X. stenophylla. In the study, it was seen that X. stenophylla can probably be an alternative to the other natural antioxidant and antibacterial agents.

Xanthoparmelia stenophylla geleneksel olarak yılan sokması ve frengi gibi zührevi hastalıkların tedavisinde kullanılmaktadır. X. stenophylla değişik renk maddelerine sahiptir ve boya kaynağı olarak da kullanılabilmektedir. X. stenophylla’dan elde edilmiş farklı ekstraktlar antioksidan ve antibakteriyal özellikleri bakımından test edildi. Ekstraktların fenol ve flavonoid konsantrasyonları da belirlendi. Soksalet ekstraksiyonunda kloroform ve aseton kullanıldı. Bakteri inhibe etme aktivitesi disk difüzyon metoduyla belirlenirken antioksidan özelliği DPPH radikal süpürme aktivitesi, indirgeme gücü, metal şelatlama aktivitesi ile belirlendi. Kloroform ekstraktı en çok Bacillus megaterium’a karşı 25 mm’lik zon inhibisyonu gösterdi. Aseton ve kloroform ekstraktlarının her ikisi de Klebsiella pneumoniae’ye karşı etki göstermedi. En yüksek fenolik içerik kloroform ekstraktında bulundu (42.58±0.47 µg/mL). Ekstraktların DPPH aktivitesi %9.33‐33.84 arasındaydı. Ekstraktların ve standartların indirgeme gücü BHT>Rutin>X. stenophylla’nın kloroform ekstraktı>X. stenophylla’nın aseton ekstraktı şeklinde bulundu. Çalışmada, X. stenophylla’nın diğer doğal antioksidan ve antibakteriyal ajanlara bir alternatif olabileceği görüldü.
Xanthoparmelia stenophylla (Ach.) Ahti&D. Hawksw. Likeninin Fenol ve Flavonoid Miktarları, Antioksidan ve Antimikrobiyal Potansiyelleri
Keywords: Xanthoparmelia stenophylla; Lichen; Antimicrobial activity; Antioxidant